PERLINDUNGAN HUKUM TERHADAP PEMBELI RUMAH AKIBAT WANPRESTASI YANG DILAKUKAN OLEH DEVELOPER DALAM PERJANJIAN PENGIKATAN JUAL BELI (STUDI KASUS PUTUSAN NOMOR 117/PDT.G/2020/PN.CBI) - Nadiyatu Ruaya Safirly; Mugiati (Constitutum: Jurnal Ilmiah Hukum, 2025)
A Sales and Purchase Agreement (PPJB) is free to contain promises from the parties. The PPJB serves as a legal basis for the parties who make it. However, in reality, not all developers carry out construction as agreed in the PPJB, so that home buyers do not receive legal protection. This study discusses the legal consequences of the PPJB for the developer's default and legal protection for home buyers due to default committed by the developer in the PPJB with a case study of Decision Number 117/Pdt.G/2020/PN.Cbi. This study uses a normative juridical research method. The results explain that the legal consequences of the PPJB due to the developer's default are null and void and the agreement is no longer valid. This is because the default committed by the developer has violated Article 1320 of the Civil Code. The agreement is considered null and void and each party is returned to its original state as before the agreement. Legal protection for buyers in PPJB due to developer default is that the buyer has the right to get back the money that has been paid to the developer and receive compensation and/or replacement with interest of 6% as regulated in Article 1250 of the Civil Code in connection with Staatsblad 1848 Number 22 of all claims for buyer losses.